Understanding Black Students' Social Agency at Historically Black Colleges: Data From a National Survey - Castro Samayoa, Andrés; Stolzenberg, Ellen Bara; Zimmerman, Hilary B.; Gasman, Marybeth (Frontiers in Education, 2018)
This manuscript considers the political attitudes of Black students at Historically Black Colleges and Universities using a 2015 sample of first-year respondents. In response to this special issue's call to consider issues of student protest at Minority Serving Institutions, our manuscript offers empirical evidence on students' political dispositions at Historically Black Colleges and Universities. Indeed, understanding the civic dispositions and political ideologies of Black students at Historically Black Colleges and Universities is not only a timely topic, but also a necessary one if we are to understand the future political engagement of an increasingly diverse nation (Lefever, 2005; Williamson, 2008).